Production of polyclonal antibodies against leek yellow stripe virus (LYSV) coat protein expressed in Escherichia coli and its application in serological diagnostics. (16th December 2022) - Gupta, Nitika; Rai, Richa; Islam, Sabina; Meena, R P; Baranwal, V K
Abstract: Leek yellow stripe virus (LYSV) is one of the most important potyviruses, associated with garlic throughout the world including India. LYSV causes stunting and yellow streaks in garlic and leek leaves and with other co-infecting viruses leading to severe symptom expression and yield reduction. In this study, we have made the first reported attempt to produce specific polyclonal antibodies to LYSV using expressed recombinant coat protein, which would be useful for screening and routine indexing of the garlic germplasm. The coat protein (CP) gene was cloned, sequenced and further subcloned in pET-28a(+) expression vector which yielded ∼35 kDa fusion protein. The fusion protein was obtained in insoluble fraction after purification and its identity was confirmed by SDS-PAGE and western blotting. The purified protein was used as immunogen for production of polyclonal antisera in New Zealand white rabbit. Antisera raised, was able to recognize the corresponding recombinant proteins in western blotting, immunosorbent electron microscopy and dot immunobinding assay (DIBA). Developed antisera to LYSV (titer 1:2000) was used for screening of 21 garlic accessions in antigen coated plate enzyme-linked immunosorbent assay (ACP-ELISA) and 16 accessions were found positive for LYSV, indicating its widespread presence within the collection tested. To the best of our knowledge, this is the first report of a polyclonal antiserum against the in-vitro expressed CP of LYSV and its successful application in diagnosis of LYSV in garlic accessions in India.